Weather analysis and forecasting : applying satellite water vapor imagery and potential vorticity analysis - Santurette, Patrick; Georgiev, Christo G. (Amsterdam ; Boston : Elsevier, 2005)
A practical training manual and guide to analyzing circulation patterns and satellite imagery to improve operational forecasting.
Weather Analysis and Forecasting; Weather Analysis and Forecasting; Contents; Preface; Acknowledgments; Introduction; Part I: Fundamentals; Part II: Practical Use of Water Vapor Imagery and Dynamical Fields; Appendix A; Appendix B; Appendix C; Appendix D; References; Index.
Includes bibliographical references (pages 171-172) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Satellite meteorology; Water vapor, Atmospheric; Weather forecasting; Météorologie par satellite; Vapeur d'eau atmosphérique.; Temps (Météorologie) -- Prévision.; NATURE -- Weather; SCIENCE -- Earth Sciences -- Meteorology & Climatology; Satellite meteorology; Water vapor, Atmospheric; Weather forecasting; dissertations; Academic theses; Academic theses; Thèses et écrits académiques.